Occurrence of high-grade glioma in Noonan syndrome: report of two cases - El-Ayadi, Moatasem; Ansari, Marc; Kühnöl, Caspar David; Bendel, Anne; Sturm, Dominik; Pietsch, Torsten; Kramm, Christof M.; Büren, André O. von (Pediatric blood & cancer, 2019)
Noonan syndrome (NS) is an autosomal dominant disorder commonly caused by PTPN11 germline mutations. Patients are characterized by short stature, congenital heart defects, facial dysmorphism, and increased risk of malignancies including brain tumors. Commonly associated brain tumors are dysembryoplastic neuroepithelial tumor and low-grade glioma. We report two cases of anaplastic astrocytoma with PTPN11-related NS. We conducted a systematic search of medical databases looking for other reported cases of high-grade glioma associated with NS and identified 24 cases of brain tumors, all of which were low-grade glial or glioneuronal tumors except for one case of medulloblastoma.
Gesehen am 04.04.2019